Molecular epidemiology of dengue, yellow fever, Zika and Chikungunya arboviruses: An update (2019)
Arboviruses are a group of viruses transmitted by arthropods. They are characterized by a wide geographic distribution, which is associated with the presence of the vector, and cause asymptomatic infections or febrile diseases in humans in both enzootic and urban cycles. Recent reports of human infections caused by viruses such as dengue, Zika, and chikungunya have raised concern regarding public health, and have led to the re-evaluation of surveillance mechanisms and measures to control the transmission of these arboviruses. Viruses such as Mayaro and Usutu are not currently responsible for a high number of symptomatic infections in humans, but should remain under epidemiological surveillance to avoid the emergence of new epidemics, as happened with Zika virus, that are associated with new or more severe symptoms. Additionally, significant variation has been observed in these viruses, giving rise to different lineages. Until recently, the emergence of new lineages has primarily been related to geographical distribution and dispersion, allowing us to ascertain the possible origins and direction of expansion of each virus type, and to make predictions regarding regions where active infections in humans are likely to occur. Therefore, this review is focused on untangling the molecular epidemiology of Dengue, Yellow fever, Zika and Chikungunya due to their recent epidemics in Latinamerica but provides an update on the geographical distribution globally of these viral variants, and outlines the need for further understanding of the genotypes/lineages assignment. © 2018 Elsevier B.V.